Falsafah Kembar Mayang Dalam Membentuk Keluarga Sakinah - Hijriyah; Katimin; Wahyu Wiji Utomo (Yayasan Bayt Shufiya Nusantara, 2025)
This study aims to explore the philosophical meaning of kembar mayang within the Javanese migrant community in Tanah Jawa, Simalungun Regency, and to examine its relevance for nurturing a sakinah family. Employing a qualitative phenomenological approach, the research collects data through observation, documentation, and interviews with traditional wedding specialists (dukun manten) and members of the local Javanese community. These findings are further supported by a literature review consisting of books, theses, dissertations, and scholarly articles addressing the symbolism of kembar mayang. Data analysis follows the stages of data reduction, data display, and conclusion drawing, interpreted through Paul Ricoeur’s philosophy of symbols to unveil the deeper layers of meaning embodied in the ritual practices and material components of kembar mayang. The results reveal that kembar mayang is preserved in its original form within the wedding practices of Javanese communities in the diaspora and continues to function as an ethical–spiritual foundation for cultivating a sakinah family. The interpretation of its materials, structure, and ceremonial use demonstrates that this tradition encapsulates philosophical teachings on relational harmony, steadfast intention, and the unification of two lives within an ordered and balanced framework.